Insights into students’ perceptions of their teachers’ instructional approaches - Subedi, Kusum Raj; Subedi, Upendra; Subedi, Suprabha (Shaheed Smriti Journal, 2021)
Teaching styles, also called teaching methods, are considered to be the general principles, and educational and management strategies for classroom instruction. At the start of the twentieth century, various teaching philosophies began to be used. The purpose of this study is to describe how the students’ perception of their teacher teaching styles in learning general management is. This is qualitative research. The samples in this research are 33 students from BBS which are randomly selected from the respective classes. Questionnaires about how students perceive their teachers’ teaching styles are utilized to collect the data. The results obtained state that the general management learning process taught in classes and the general student learning experience are still teacher-centered. Based on the research conducted, it can be concluded that learning activities at Shaheed Smriti Multiple Campus are teacher-centered and students are still passive learners. This can be inferred from the number of students who agree and strongly agree with the questionnaire statement that the learning applied by teachers in the classroom is teacher-centered and that students are passive learners.